2014
DOI: 10.1371/journal.pone.0087770
|View full text |Cite
|
Sign up to set email alerts
|

Brown Norway Chromosome 1 Congenic Reduces Symptoms of Renal Disease in Fatty Zucker Rats

Abstract: We previously reported that a congenic rat with Brown Norway (BN) alleles on chromosome 1 reduces renal disease of 15-week old fatty Zucker rats (ZUC). Development of renal disease in fatty BN congenic and fatty ZUC rats from 9 through 28 weeks is now examined. Analysis of urine metabolites by 1H nuclear magnetic resonance (NMR) spectroscopy revealed a significantly increased urinary loss of glucose, myo-inositol, urea, creatine, and valine in ZUC. Food intake was lower in the BN congenic rats at weeks 9–24, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Chow-fed males develop a mild form of T2D, have significantly elevated plasma triglycerides and develop phenotypes of mild to moderate renal disease [ 13 ]. In the UC Davis male ZUC colony, T2D related traits were primarily the presence of glucose in urine and elevated fasted glucose levels [ 9 , 14 , 15 ]. Renal disease markers included increases of urinary albumin excretion and urine volume with age [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chow-fed males develop a mild form of T2D, have significantly elevated plasma triglycerides and develop phenotypes of mild to moderate renal disease [ 13 ]. In the UC Davis male ZUC colony, T2D related traits were primarily the presence of glucose in urine and elevated fasted glucose levels [ 9 , 14 , 15 ]. Renal disease markers included increases of urinary albumin excretion and urine volume with age [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the UC Davis male ZUC colony, T2D related traits were primarily the presence of glucose in urine and elevated fasted glucose levels [ 9 , 14 , 15 ]. Renal disease markers included increases of urinary albumin excretion and urine volume with age [ 14 ]. Our previous studies have demonstrated that ovariectomy decreases and estrogen increases urinary albumin excretion in female UC Davis Zucker rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations